2011
DOI: 10.1158/0008-5472.can-11-1271
|View full text |Cite
|
Sign up to set email alerts
|

A Novel MLL5 Isoform That Is Essential to Activate E6 and E7 Transcription in HPV16/18-Associated Cervical Cancers

Abstract: Human papillomavirus (HPV) is the primary cause of human cervical cancer. The viral proteins E6 and E7 are essential to transform noncancerous epithelial cells into cancerous carcinomas by targeting key tumor suppressors p53 and retinoblastoma (Rb) proteins, respectively, but the cellular factors involved in E6 and E7 transcription themselves are incompletely understood. In this study, we defined a novel isoform of the mixed lineage leukemia 5 gene (MLL5b) as a specific and critical regulator of E6 and E7 tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…Yew et al previously identified an isoform of mixed lineage leukemia 5 (MLL5β), which regulates HPV E6/E7 oncogene transcription through its interaction with AP-1 at the 5′ segment of the HPV16/18 long control region (LCR) (29). Interestingly, Nin et al (30) reported that MLL5β was O-GlcNAcylated at T440 residue and this modification is necessary for its interaction with AP-1 and its recruitment to the HPV16/18-LCR.…”
Section: Discussionmentioning
confidence: 99%
“…Yew et al previously identified an isoform of mixed lineage leukemia 5 (MLL5β), which regulates HPV E6/E7 oncogene transcription through its interaction with AP-1 at the 5′ segment of the HPV16/18 long control region (LCR) (29). Interestingly, Nin et al (30) reported that MLL5β was O-GlcNAcylated at T440 residue and this modification is necessary for its interaction with AP-1 and its recruitment to the HPV16/18-LCR.…”
Section: Discussionmentioning
confidence: 99%
“…34 To date, several other isoforms listed in supplemental Table 3 have been reported besides MLL5. 35,36 Strikingly, compared with the other isoforms, NKp44L is characterized by a specific exon (21spe) at the C-terminus, probably implicated in its unique subcellular localization, as compared with the other MLL proteins. Importantly, the mRNA expression profiles of MLL5 and NKp44L are very different, pleotropic for MLL5, but significantly more restrictive to tumor cells for NKp44L.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified a novel MLL5 isoform, MLL5b, which was found to activate E6/E7 expression in HPV16/18-positive cells through the distal AP-1 site in the LCR (33). Knocking down MLL5b via a siRNA-duplex designed specifically to target only the isoform, downregulated E6 and E7, at both transcript and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that MLL5b is essential in the activation of both the E6 and E7 transcription in HPV16/18-positive cells (33). With these observations, we hypothesized that the more pronounced antitumor effects of MLL5b-targeted silencing in HeLa cells was due to the combined effects of both apoptosis and senescence as a consequence of the downregulation of both E6 and E7 transcript levels.…”
Section: Targeted Silencing Of Mll5b Reduces the Colonyforming Abilitmentioning
confidence: 90%
See 1 more Smart Citation